Identifikasi Perubahan Penggunaan Lahan pada Sub DAS Karang Mumus Provinsi Kalimantan Timur - Jannah, Miftahul; Fadlin, Feri; Widyasasi, Dyah; Suparjo, Suparjo (P3KM Politani Samarinda, 2023)
This research is motivated by the growth of population and its activities. The increasing population and the more intensive activities of people in a place have an impact on changes in land use. One thing shown is changes in the Karang Mumus River Watershed (DAS) sub-area in Samarinda. Samarinda is one of the cities that is developing with a population that is increasing every day and has a variety of urban activities which are not small, causing the need for space is also not small. This research aims to identify land use and land use changes in the Karang Mumus sub-watershed. The method used in this research is the Geographic Information System (GIS) method, to process and analyze data so as to obtain information, types of land cover, area and changes in land use in the Karang Mumus sub-watershed in 1990, 2000, 2011 and 2020. Results from this research, over the past three decades, there has been a significant decrease in the area of dry land forests, while residential areas and the mining sector have seen rapid growth. The loss of dry land forests potentially disrupts ecological functions, including carbon absorption and serving as habitats for various species, which can impact ecosystem health and biodiversity. The expansion of residential areas and mining without proper management and planning poses environmental risks, including erosion, pollution, and potential degradation of water resources and air quality.